Moving Up the "Magic Moment": Fathers' Experience of Prenatal Ultrasound - Walsh, Tova B.; Tolman, Richard M.; Davis, R. Neal; Palladino, Christie L.; Romero, Vivian C.; Singh, Vijay (Fathering (Harriman, Tenn.), 2014)
Expectant fathers in the U.S. frequently accompany their partner to a prenatal ultrasound, yet little is known about how fathers experience ultrasound attendance. This is an important knowledge gap because studies have shown strong and consistent associations between a father's prenatal and postnatal involvement, and efforts to actively engage fathers at ultrasound may have longitudinal impact. We conducted semi-structured interviews with 22 fathers after ultrasound, analyzed data using principles of grounded theory, and built a conceptual model of how fathers experience ultrasound. Results suggest that ultrasound attendance contributes to paternal feelings of connection to the unborn baby and motivation to change behavior. Ultrasound appointments may offer an opportunity to engage men to promote positive partnering and parenting across the lifespan.